Subtunical Reduction Clitoroplasty of a 22 years old Female for Clitoromegaly with Congenital Adrenal Hyperplasia-Case Report - Khan, Mohammad Saneat Jahan; Asma, Khaleda; Zesmine, Fahmida; Alam, Md Shafiqul; Khan, Mosabbir Ahmad; Khanam, Shifa (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Clitoromegaly is an abnormal condition commonly related to congenital adrenal hyperplasia. We presented a 22 years old adult female patient with chief complaint of enlarged clitoris since birth, other female secondary sexual characteristics were normal. The karyotype test result was 46 XX. Subtunical resection of erectile cavernous tissue of the enlarged clitoris with preservation of intact blood supply to the glans is a safe method of diminishing shaft and glans size and allow the patient to do sexual activity after marriage during a two-years follow up. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(2):127-130.